TRAUMATIC BONE CYST TRAUMATIC BONE CYST OF THE MANDIBLE: CASE REPORTOF THE MANDIBLE: CASE REPORT - Elitsa Deliverska (Peytchinski Publishing, 2020)
Background: Idiopathic bone cavities (IBCs) are osseous pseudocysts with unclear etiology. Their clinical course and response to treatment are poorly understood. Purpose: The aim of this study is to present a case of a patient with IBC with long-term follow-up. Patients and Methods: A retrospective case of 16- years old male patient with IBC of the jaw is implemented. Medical records of the patient were reviewed for data on presentation and imaging. The patient underwent surgical exploration to confirm the diagnosis. Follow-up radiographs were evaluated for resolution or persistence after the procedure. Results: The lesion was asymptomatic and discovered as incidental findings. Common radiographic features included scalloping without root resorption or displacement and cortical thinning in lingual aspect expansion. Intraoperative findings showed an empty bone cavity often filled with blood-tinged serous fluid or blood. The histopathology of scrapings from the bony wall showed benign mixed fibrous tissue and no epithelial lining. Radiographic follow-up was 3 years after surgery. After exploration and curettage, the patient had a complete bone fill. Conclusion: IBC is a rare condition, and several differential diagnosеs should be considered. A single procedure to confirm the diagnosis and curettage is sufficient for management.